Macroprudential regulation of investment funds - Giovanni Di Iasio; Christoph Kaufmann; Florian Wicknig (European Central Bank (ECB), 2022)
The investment fund sector, the largest component of the non-bank financial system, is growing rapidly and the economy is becoming more reliant on investment fund financial intermediation. This paper builds a dynamic stochastic general equilibrium model with banks and investment funds. Banks grant loans and issue liquid deposits, which are valuable to households. Funds invest in corporate bonds and may hold liquidity in the form of bank deposits to meet investor redemption requests. Without regulation, funds hold insufficient deposits and must sell bonds when hit by large redemptions. Bond liquidation is costly and eventually reduces investment funds' intermediation capacity. Even when accounting for side effects due to a reduction of deposits held by households, a macroprudential liquidity requirement improves welfare by reducing bond liquidation and by increasing the economy's resilience to financial shocks akin to March 2020.
Keywords: E44; G18; G23; 330; Non-Bank Financial Intermediation; Macroprudential Policy; Liquidity Regulation